Translating Attitudes toward Sexism in Gone Girl Novel (An Appraisal Theory Approach) - Nuraisiah, Siti; Nababan, Mangatur Rudolf; Santosa, Riyadi (Lingua Cultura, 2018)
The research dealt with attitudes toward sexism. It aimed to know the translation technique and quality in terms of accuracy and acceptability. It deployed a descriptive qualitative method. The data were obtained from a novel titled Gone Girl and the copy of the novel in Indonesian translation through content analysis and focus group discussion. The data were analyzed through domain, taxonomy, and componential analysis to reveal cultural value. The research indicates that translation techniques determine its qualities. It reveals that established equivalence results in the good quality of translation while the generalization, discursive creation, explicitation, modulation, literal translation, particularization, and description reflect quite good and bad quality of the translation. Moreover, the application of generalization and explicitation results in non-sexist translation. Consequently, the translator becomes less sexist than writer and gives readers different effect with the original one. However, this is affected by some factors; the translator’s subjectivity, translator’s competence, linguistic characteristic differences, and social-cultural differences.